Modelling the age-related trajectory of performance in Para swimmers with physical, vision and intellectual impairment - Hogarth, L.; Nicholson, V.; Payton, C.; Burkett, B. (Scandinavian Journal of Medicine & Science in Sports, 2021)
This study is the first to provide information on the age-related trajectories of performance in Para swimmers with physical, vision and intellectual impairment. Race times from long-course swim meets between 2009 and 2019 were obtained for Para swimmers with an eligible impairment. A subset of 10 661 times from 411 Para swimmers were included in linear mixed effects modelling to establish the relationship between age and performance expressed relative to personal best time and world record time. The main findings were: (a) age has the most noticeable influence on performance between the ages of 12-20 years before performances stabilize and peak in the early to late twenties, (b) women have faster times relative to personal best and world record time than men during early adolescence and their performances stabilize, peak and decline at younger ages, and (c) Para swimmers from different sport classes show varying age-related trajectories in performance after maturation and when training-related factors are more likely to explain competitive swim performance. The results of this study can guide talent identification and development of Para swimmers at various stages of their career and help to inform decision-making on the allocation of sport class and sport class status in Para swimming classification.